MANAGEMENT INCREASED INTRACRANIAL PRESSURE IN PATIENTS WITH STROKE AND BRAIN TUMOR - Cut Husna (Fakultas Keperawatan-Universitas Syiah Kuala, 2011)
ABSTRACTManagement increased intracranial pressure (IICP) in stroke and brain tumor patients consists of pharmacotherapy and non-pharmacotherapy. Pharmacotherapy intervention comprises hyperosmolar therapy, euglycemia, hyperventilation and normocapnia, optimal oxygenation, controlling cerebralmetabolism (sedation), anticonvulsant prophylaxis, and maintenance of normothermia, Furthermore, nonpharmacotherapy consist of positioning of head on bed position 15-30 degrees, initial trauma asessment (airway, breathing, and circulation), suctioning, control fluid and electrolytes, and nutrition need. The design of study was descriptive explorative for three patients in Songkla Nagarind Hospital, Hatyai, Thailand. The aim of the study was to describe management increased intracranial pressure in patients withstroke and brain tumor patients by using three questionnaires that consisted of Demographic Data Questionnaire (DDQ), Management of IICP Questionnaire (MIQ), and Glasgow Coma Scale (GCS). Data collection was conducted for three patients hospitalized with stroke (1 case) and brain tumor (2 cases). The study was analyzed by using descriptive statistic with mean (x) and standard deviation (SD). The results of the study showed that management of IICP in those patients was good, and the Glasgow Coma scale (GCS) was delirious (1 case) and consciousness (2 cases). The study recommended that to caring the patients with IICP, the nurses must monitor for Cushing triad (hypertension, bradycardia, and bradypnea), vital signs, neurological signs, risk for ischemia cerebral, potential hyperthermia, fluid imbalance, and pain post surgical incision (craniotomy and V/P shunt) particularly for brain tumor patients and hydrocephalus.Keywords: knowledge, abortus, related factors of abortus